MODERN VITAMIN AND MINERAL COMPLEXES AND THEIR INFLUENCE ON THE IMMUNE RESPONSE IN CHILDREN - I.A. Gromov; R.M. Torshkhoeva; A.A. Alekseeva; L.S. Namazova (Педиатрическая фармакология)
As population based studies conducted in Russia showed, deficit of vitamins and microelements is quite widespread among the population, and children are no exclusion. The article demonstrates the functions of these compounds that are essential for the normal operation of the body — their antioxidant and immunomodulatory activities, as well as the consequences of their deficit. Besides, authors explain persuasively the advisability of use of the new combined drug, which includes vitamins, microelements and probiotics, and demonstrated its high efficiency in terms of clinical study.Key words: vitamins, microelements, probiotics, properties, deficit, deficit reduction, children.